Immediate Loading of Tapered Implants Placed in Postextraction Sockets and Healed Sites. Issue 5 (July 2016) - Han, Chang-Hun; Mangano, Francesco; Mortellaro, Carmen; Park, Kwang-Bum
Abstract : Objective: The aim of the present study was to compare the survival, stability, and complications of immediately loaded implants placed in postextraction sockets and healed sites. Methods: Over a 2-year period, all patients presenting with partial or complete edentulism of the maxilla and/or mandible (healed site group, at least 4 months of healing after tooth extraction) or in need of replacement of nonrecoverable failing teeth (postextraction group) were considered for inclusion in this study. Tapered implants featuring a nanostructured calcium-incorporated surface were placed and loaded immediately. The prosthetic restorations comprised single crowns, fixed partial dentures, and fixed full arches. Primary outcomes were implant survival, stability, and complications. Implant stability was assessed at placement and at each follow-up evaluation (1 week, 3 months, and 1 year after placement): implants with an insertion torque (IT) <45 N·cm and/or with an implant stability quotient (ISQ) <70 were considered failed for immediate loading. A statistical analysis was performed. Results: Thirty implants were placed in postextraction sockets of 17 patients, and 32 implants were placed in healed sites of 22 patients. There were no statistically significant differences in ISQ values between the 2 groups, at each assessment. In total, 60 implants (96.8%) had an IT ≥45 and an ISQ ≥70 at placement and at each follow-up control: all these implants were successfully loaded. Only 2 implants (1 in a postextraction socket and 1 in a healed site, 3.2%) could not achieve an IT ≥45 N·cm and/or an ISQ ≥70 at placement or over time: accordingly, these were considered failed for stability, as they could not be subjected to immediate loading. One of these 2 implants, in a healed site of a posterior maxilla, had to be removed, yielding an overall 1-year implant survival rate of 98.4%. No complications were reported. No significant differences were reported between the 2 groups with respect to implant failures and complications. Conclusion: Immediately loaded implants placed in postextraction sockets and healed sites had similar high survival and stability, with no reported complications. Further long-term studies on larger samples of patients are needed to confirm these results.